Perancangan Sistem Pendaftaran Siswa Baru Secara Online Pada SMK Miftahul Jannah Cikupa - Rahayu, Sri; Setiadi, Ade; Muryanto, Alim (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2021)
The corona virus (COVID-19) has recently shocked the whole world, including Indonesia. even Indonesia is included in the 30 countries with the most spread of the virus in the world. The rapid spread of the corona virus (COVID-19) has made educational institutes stop imposing face-to-face learning, so students have to study online at their respective homes. In the new school year students who have graduated from the previous school must choose the school to go to next. however, many schools are still not ready to deal with the buildup of prospective new students and have not fully implemented the daily COVID-19 protocol. Therefore, a new online student registration system was created at SMK Miftahul Jannah Cikupa to avoid physical contact and the accumulation of prospective new students at the school location. In this study the authors used several research methodologies, namely data collection methods including observation, interviews, and literature studies, analysis methods using SWOT analysis, system design methods using prototypes, and testing methods using blackbox testing. The results obtained in this study are that new prospective students do not need to come directly to the school, simply access them via a smartphone or laptop at their respective homes to register online and fill out the forms that are available on the website, and upload the required files. Keywords: System, Online Registration, COVID-19